Fixed point for mappings of asymptotically nonexpansive type in Lebesgue spaces with variable exponents - Benavides, Tomas Domínguez (Topological Methods in Nonlinear Analysis, 2024)
Assume that $(\Omega, \Sigma, \mu)$ is a $\sigma$-finite measure space and$p\colon\Omega\to [1,\infty]$ a variable exponent. In the case of a purely atomic measure, we prove that the w-FPP for mappings of asymptotically nonexpansive type in the Nakano space $\ell^{p(k)}$, where $p(k)$ is a sequence in $[1,\infty]$, is equivalent to several geometric properties of the space, as weak normal structure, the w-FPP for nonexpansive mappings and the impossibility of containing isometrically $L^1([0,1])$. In the case of an arbitrary $\sigma$-finite measure, we prove that this characterization also holds for pointwise eventually nonexpansive mappings.To determine if the w-FPP for nonexpansive mappings and for mappings of asymptotically nonexpansive type are equivalent is a long standing open question \cite{Ki3}. According to our results, this is the case, at least, for pointwise eventually nonexpansive mappings in Lebesgue spaces with variable exponents.